PEMBELAJARAN MATEMATIKA MENGGUNAKAN MEDIA KOMIK KELAS VIII - Nicolas Samuel Panggabean; Hamdani Asep; Asep Nursangaji (Universitas Tanjungpura, 2022)
AbstractLaw of the Republic of Indonesia Number 20 of 2003 concerning the National EducationSystem article 40 paragraph 2a states that: